How does t^2-2t-1=0 become t=1+-sqrt2?
2 Answers
May 29, 2018
Explanation:
"solve for t using the method of "color(blue)"completing the square"
• " the coefficient of the "t^2" term must be 1 which it is"
• " add "(1/2"coefficient of the t- term ")^2" to both sides"
"add 1 to both sides"
t^2-2t=1
t^2+2(-1)t color(red)(+1)=1color(red)(+1)
(t-1)^2=2
color(blue)"take the square root of both sides"
sqrt((t-1)^2)=+-sqrt2larrcolor(blue)"note plus or minus"
t-1=+-sqrt2
"add 1 to both sides to obtain"
t=1+-sqrt2
May 30, 2018
An alternate way using the quadratic formula:
Explanation:
Another way to find solutions for
with